Effect of physical restraint on glucose tolerance in cynomolgus monkeys. Issue 3 (9th February 2013) - Shirasaki, Yasufumi; Yoshioka, Naoya; Kanazawa, Kanpei; Maekawa, Tsuyoshi; Horikawa, Tadahiro; Hayashi, Toshiaki
Abstract Background Physiologic stress has been demonstrated to impair glucose tolerance. Methods Glucose tolerance tests were performed using six cynomolgus monkeys. Results Chair‐restrained subjects elicited higher elevations of plasma glucose and cortisol compared with squeezing device‐restrained subjects. Conclusions The responses to a glucose challenge are altered by different restraint procedures.